Degradation of imazalil, orthophenylphenol and pyrimethanil in Clementine mandarins under conventional postharvest industrial conditions at 4 °C. (1st March 2016) - Besil, Natalia; Pérez-Parada, Andrés; Cesio, Verónica; Varela, Pablo; Rivas, Fernando; Heinzen, Horacio
Highlights: A validated method for fungicide residue determination was developed. The dissipation of three postharvest citrus fungicides in mandarins under conventional industrial cold storage was studied. Four different application technologies were tested. The half life of pyrimethanil, imazalil and orthophenylphenol at 4 °C was determined. Abstract: The degradation of the postharvest fungicides imazalil, orthophenylphenol, and pyrimethanil was studied on Clementine mandarins during packinghouse storage for a 28 day period at 4 °C. Fruits to which orthophenylphenol was applied, were treated with imazalil and pyrimethanil at doses of 1000 and 2000 mg L −1, using cascade application for the later and cascade and wax for the former. The decay of the three fungicides was evaluated using an in-house validated analytical procedure that includes the extraction and dispersive clean up of the samples followed by the GC–MS determination of the pesticide residues. The impact of fruit storage time on pesticide residues concentration was assessed. The residues found for the different application technologies were always below the established Maximum Residue Limits by the Codex Alimentarius and the European Union (5 mg kg −1 for imazalil, 7 and 8 mg kg −1 for pyrimethanil, and 10 mg kg −1 and 5 mg kg −1 for orthophenylphenol). The fungicides dissipated differentially. Pyrimethanil showed little degradation, if any, at both tested concentrations, but the half-life of imazalil on the fruit was 15–18 days, independent of the application technology. Orthophenylphenol dissipated with a half-life of 15 days. The initial imazalil residue found after cascade treatment was not significantly different between the doses studied ( p  < 0.5), whereas when the fungicide was included in wax as an emulsifiable concentrate the initial and final imazalil residues were significantly different. Final residue levels after 28 days of storage were 0.12–0.24 mg kg −1 for imazalil, 0.68 mg kg −1 for 2-phenylphenol and 0.56 mg kg −1 for pyrimethanil for all the evaluated treatments.